EFFECT OF VENTURI DIAMETER OF CARBURETOR ON PERFORMANCE OF SIX-STROKE 125 CC COMBUSTION ENGINE - Eko Siswanto; Agung Sugeng Widodo; Nurkholis Hamidy; Denny Widhiyanuriyawan; Gilang Rausan Fikri Noor (Journal of Environmental Engineering and Sustainable Technology, 2016)
Performance of six stroke single power combustion engine affected by venturi diameter of carburetor is presented. This study is to begin on development of six-stroke single power of combustion engine (CE). Developing of this six stroke CE is based on addition of duration on both mass- and thermal diffusion, and on mixing time before the combustion. Evaluation of the six-stroke CE performance is done via enlarge venturi diameter of carburetor. Selected venturi diameters are 18 (mm) and 20 (mm). Fuel of the CE is gasoline-based using research octane number (RON) of 92. Interval of each ascending rotation speed is 400 (rpm), and observation was done using a constant throttle aperture 30 (%). The observed performances of the 125 (cc) six-stroke CE is then compared using a convensional four-stroke 125 (cc), as well. It informs that diameter 20 (mm) can increase average of about 21(%) on torsion, 21 (%) on power, 16 (%) on specific fuel consumption (SFC), and 23 (%) on thermal efficiency to that of the diameter 18 (mm). If compared to four-stroke CE, the six-stroke CE has lower in SFC and thermal efficiency, however, it has higher in average value of torsion, power, and engine speed, respectively about 15 (%).